Heidi Fleiss Hollywood Madam - Broomfield, Nick (Lafayette Film, 1995)
In her heyday Heidi Fleiss was at the center of a highly successful prostitute ring. The most interesting part of her business was the fact that her clientele reportedly comprised various Hollywood stars. Who can forget her legendary black book? Labeled "Madam to the Stars," this fascinating documentary exposes her world. Includes interviews with Heidi and retired L.A. police detective Daryl Gates.